2015
DOI: 10.15384/kjhp.2015.15.1.31
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Awareness and Knowledge of Energy Drinks on Consumption Patterns among College Students

Abstract: Background:We examined the consumption patterns and the knowledge and awareness of energy drinks to draw up a guideline for energy drink consumption and to give accurate information to college student. Methods: Data from 324 subjects (186 males and 138 females) were collected using self-administered questionnaires. The study participants were recruited from the Gyeonggi-do, Seongnam area between March and June 2013. Results:The results showed that there was a significant gender-based difference in awareness of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 18 publications
2
10
0
Order By: Relevance
“…Moreover, a recent study showed that, taste-driven consumers (31%) endorsed pleasurable taste, energy-seeking consumers (24%) endorsed function and taste motives, and hedonistic consumers (33%) endorsed pleasure and sensation-seeking motives [19]. Additional reasons for energy drink consumption were for enhanced fatigue recovery (79.9%) concentration enhancement (29.3%) and curiosity (22.0%) [3].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, a recent study showed that, taste-driven consumers (31%) endorsed pleasurable taste, energy-seeking consumers (24%) endorsed function and taste motives, and hedonistic consumers (33%) endorsed pleasure and sensation-seeking motives [19]. Additional reasons for energy drink consumption were for enhanced fatigue recovery (79.9%) concentration enhancement (29.3%) and curiosity (22.0%) [3].…”
Section: Discussionmentioning
confidence: 99%
“…The consumption rates in this demographic are increasing primarily because of the concentration enhancement and fatigue-relieving effects of energy drinks [3], yet there is relatively little information regarding the safety and quality of these products. In addition, much of the available information about energy drinks can be vague and misleading to consumers.…”
Section: Introductionmentioning
confidence: 99%
“…Awareness about energy drink did not correlate well with knowledge among young adults. Unexpectedly, the positive awareness about energy drink among students prompted them towards more consumption [36]. This might be due to the marketing strategies adopted by selling companies to attract their target groups with a message of positive effects regarding their health and social image [37].…”
Section: Awareness and Knowledge About Energy Drinkmentioning
confidence: 99%
“…The main source of information for caffeine and energy drink intake among students is media and commercials. In addition, to get the reliable information, the adolescent also prefers parents, followed by doctor and teacher [36,39]. Some other factors like social situations and spending time with friends is being considered as a common reason for energy drink consumption in young adult [40].…”
Section: Source Of Information About Energy Drink and Preferred Brandmentioning
confidence: 99%
“…As the global market for energy drinks approaches nearly $15 trillion, the general consumption of energy drinks has increased accordingly, particularly among college students. The consumption rates among this demographic are increasing because of the concentration enhancement and fatigue-relieving effects of energy drinks [5], yet there is relatively little information regarding the safety and quality of these products. In addition, information on the use of energy drinks among students is vague and misleading.…”
Section: Introductionmentioning
confidence: 99%